DENTAL DIASTEMAS: AESTHETIC RESOLUTION COMBINING TEETH WHITENING AND RESTORATIONS WITH DIRECT-APPLICATION COMPOSITE RESIN - CASE REPORT (CIPEEX, 2025)
Nowadays, physical appearance and self-image are related to individuals' well-being and self-esteem. Any changes that occur can have an unfavorable impact on people's appearance, leading them to seek solutions that restore their aesthetics. Diastemas are spaces or absences of consecutive dental contacts, with ethnic or genetic etiology, which may or may not be well tolerated by individuals. To close or reduce them, direct-use composite resin can be used without causing wear. Objective: To report the clinical case of a patient with yellow teeth and anterior superior diastemas, through teeth whitening and diastema closure with composite resin using the direct technique, to improve his self-image. Clinical case report: Patient DES, male, sought treatment at the UNIEVANGÉLICA Dental Clinic, complaining that "his teeth are yellow and he finds the spaces between them ugly." The intraoral clinical examination revealed excellent oral hygiene, physiologically yellowed teeth throughout, and diastemas between the anterior superior teeth. The proposed treatment was initially teeth whitening using the in-office technique, followed by the closure of the diastemas with composite resin using the direct technique. In another session, finishing and polishing were performed. Conclusions: In the era of minimally invasive philosophy, the use of whitening techniques and closing diastemas with composite resin are conservative procedures that provide aesthetic improvements in a short period of time and at an affordable cost.
Keywords: Diastema; Dental Aesthetics; Teeth Whitening; Composite Resins